Innovation and interculturalism are important features of future teachers’ training in modern society - Ostrovsky, Oleksandr; Ostrovska, Marianna; Margitich, Kateryna (Edelweiss Applied Science and Technology, 2024)
The processes of globalization, the formation of a post-industrial society, the European integration aspirations of Ukraine and the integration of the Ukrainian education system into the European educational space set the pedagogical science the task of bringing the traditional scientific apparatus into line with the system of pedagogical concepts generally accepted in Europe. The developing Ukrainian society needs highly educated people with appropriate professional and general competences who can independently make responsible decisions in a choice situation, predicting their possible consequences, capable of cooperation, distinguished by mobility, dynamism, constructiveness, a developed sense of responsibility for the fate of the country. Decisions and programs aimed at the implementation of scientific achievements, civilizational and cultural trends are implemented through the activities of subjects who perceive them. In this connection, the level of requirements of modern society for the activity and training of teachers in higher education institutions is increasing. Strengthening the integrative and cultural status of education dictates the need to train pedagogical staff capable of realizing its cultural focus. The needs of modern educational practice create the need for cross-cultural training of the future teacher of the Ukrainian language and literature, who not only acts as a mediator between the student and culture, but also contributes to the formation of the young generation’s readiness to live and act in an open intercultural space of general civilization.